Sex Steroidal Hormones and Respiratory Control - Behan, Mary (2008)
There is a growing public awareness that sex hormones can have an impact on a variety of physiological processes. Yet, despite almost a century of research, we still do not have a clear picture as to the effects of sex hormones on the regulation of breathing. Considerable data has accumulated showing that estrogen, progesterone and testosterone can influence respiratory function in animals and humans. Several disorders of breathing such as obstructive sleep apnea (OSA) and sudden infant death syndrome (SIDS) show clear sex differences in their prevalence, lending weight to the importance of sex hormones in respiratory control. This review focuses on questions such as: How early do sex hormones influence breathing? Which is the most effective? Where do sex hormones exert their effects? What mechanisms are involved? Are there age-associated changes? A clearer understanding of how sex hormones influence the control of breathing could enable sex- and age-specific therapeutic interventions for diseases of the respiratory control system.